Hypertensive disorders of pregnancy, neonatal outcomes and offspring developmental delay in Japan: The Tohoku Medical Megabank Project Birth and Three‐Generation Cohort Study - Geng Chen; Mami Ishikuro; Hisashi Ohseto; Keiko Murakami; Aoi Noda; Genki Shinoda; Masatsugu Orui; Taku Obara; Shinichi Kuriyama (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Developmental delay at an early age indicates the probability of continued problems after school age. Hypertensive disorders of pregnancy (HDP) are associated with developmental delays in offspring, with inconsistent outcomes. Neonatal outcomes vary according to HDP exposure and are relevant to development in later years. Here we aimed to clarify the relationship between HDP and developmental delay in offspring and whether neonatal outcomes mediate this association. Material and methods We used data from 5934 mother–child pairs from the Tohoku Medical Megabank Project Birth and Three‐Generation Cohort Study, a prospective cohort study conducted in Japan between July 2013 and March 2017. The Ages and Stages Questionnaires, third edition, at 24 and 42 months of age, measured developmental delay in five areas. We performed multivariate quasi‐Poisson regression and causal mediation analysis by neonatal outcomes. Results At 24 months of age, compared to offspring born from normotensive mothers, offspring born from HDP‐affected mothers were more likely to experience developmental delay (risk ratio [RR] 1.29, 95% confidence interval [CI]: 1.09–1.52) in the areas of communication (RR 1.21, 95% CI: 1.00–1.45) and personal‐social (RR 1.15, 95% CI: 1.03–1.28). This association was mediated by neonatal outcomes: preterm birth, neonatal asphyxia, NICU admission, and neonatal small head circumference. No association was observed between HDP and developmental delay at 42 months of age. Conclusions Exposure to HDP during fetal life is associated with offspring developmental delay. This association is partly mediated by neonatal outcomes.